Non-Observance of Grice’s Maxims in Political Speech: A Pragmatic Analysis of Gibran Rakabuming Raka’s Interview - Setefani, Resa; Zahra, Hilya Fitriatuz; Agus, Cecep (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the non-observance of Grice’s Cooperative Principle in an interview with Indonesian politician Gibran Rakabuming Raka, focusing on how maxim flouting functions as a pragmatic strategy in political communication. Using a qualitative approach, a publicly available interview video was selected, repeatedly viewed, and fully transcribed. The data were identified and categorized according to Grice’s four maxims quantity, quality, relevance, and manner and each instance was analyzed to uncover its conversational implicature by considering situational context, speaker intention, and shared knowledge between speaker and interviewer. The findings indicate that the dominant pattern is flouting rather than other types of non-observance (e.g., violating, infringing, opting out, or suspending). Flouting the maxim of quantity appears in extended explanations that emphasize preparedness and workload; flouting relevance emerges when sensitive or potentially risky questions are answered with broader policy frames; flouting quality occurs through evaluative claims and metaphorical wording that downplays controversy; and flouting manner is realized through vague, bureaucratic, or technical expressions that reduce directness. Overall, these pragmatic choices help project professionalism, maintain political harmony, and manage public perceptions while still allowing listeners to infer intended meanings. This study contributes to pragmatics by showing how maxim non-observance can serve as an effective rhetorical resource in Indonesian political discourse